Wool cortisol as putative retrospective indicator of stress in ewes during the third trimester of pregnancy, and their newborns: effects of parity and litter size — an exploratory study - Zeinstra, Elly C.; Vernooij, Johannes C.M.; Bentvelzen, Mireille; van der Staay, F. Josef; Nordquist, Rebecca E. (Frontiers in Animal Science, 2023)
Stress is an important factor in animal welfare. Hair or wool cortisol concentrations are considered potential long-term indicators of stress experienced by an animal. Using Swifter sheep, we investigated whether ewe parity and litter size affect wool cortisol concentrations in ewes and their offspring. We hypothesized that multiparous ewes and their offspring would have higher wool cortisol concentrations than primiparous ewes and their offspring; ewes with larger litters and their offspring would have lower wool cortisol concentrations than ewes with smaller litters and their offspring (in line with Gardner et al., 2004); male lambs would have higher wool cortisol concentrations than female lambs; and that wool cortisol concentrations in the wool of ewes and their lambs would be correlated. Lamb wool grows in utero during the third trimester of pregnancy. In ewes, the shave-reshave method was used so that wool samples from ewes also covered approximately the last trimester of pregnancy. Our study confirmed that litter size affected ewe cortisol concentrations: ewes that gave birth to larger litters (3-4 lambs) had higher wool cortisol concentrations than ewes that gave birth to smaller litters (1-2 lambs). There was no evidence that the cortisol concentrations of the ewes and their lambs were correlated. Neither litter size nor parity of the ewe affected wool cortisol in the lambs. Our study confirms that wool cortisol can be reliably measured in ewes and their newborn lambs and suggests that it may be useful as a retrospective indicator of stress during the last trimester of pregnancy.